Visualizing the Phronetic Organization: The Case of Photographs in CSR Reports - Rämö, Hans (2011)
Aspects of phronetic social science and phronetic organization research have been much debated over the recent years. So far, the visual aspects of communicating phronesis have gained little attention. Still organizations try to convey a desirable image of respectability and success, both internally and externally to the public. A channel for such information is corporate reporting, and particularly CSR reporting embrace values like fairness, goodness, and sustainability. This study explores how visual portrayals of supposedly wise and discerning values (phronesis) are used to reinforce the verbal features of CSR reporting. The two propositions underlying this study is (1) that visual images form some of the major parts of the structures of contemporary corporate reporting (particularly CSR reporting) and (2) that phronetic action in organizations is subjected not only to textual documentation, but also to visual expressions. This study also discusses how the Aristotelian concept of phronesis can be linked to contemporary concerns about responsibility, and how this is visually represented in CSR reporting. Finally, this study addresses the symbolic and contextual signification of images in corporate accounts of wisdom and responsibility.
Keywords: Wisdom; Visual communication; Responsibility; Phronesis; Photographs; CSR reporting